2018
DOI: 10.1093/biolre/ioy062
|View full text |Cite
|
Sign up to set email alerts
|

Lineage specification revealed by single-cell gene expression analysis in porcine preimplantation embryos†

Abstract: After zygotic genome activation and lineage specification, zygotes develop into late blastocysts comprising three distinct cell types. The molecular mechanisms underlying this progress are largely unknown in pigs. Here, we intended to analyze an extensive set of regulators at the single-cell level to define the events involved in the development of the porcine blastocysts. Using a quantitative microfluidics approach in single cells, we detected mRNA levels of 96 genes known to function in early embryonic devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…Recent studies of porcine embryo had verified a number of common markers and discovered pig-specific lineage markers [ 20 , 21 , 22 ]. We have identified the trends of the marker gene expression in the porcine embryos ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies of porcine embryo had verified a number of common markers and discovered pig-specific lineage markers [ 20 , 21 , 22 ]. We have identified the trends of the marker gene expression in the porcine embryos ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…In porcine in vivo embryo, lineage-specific characteristics were identified by single-cell analysis. Using single cell qPCR, stage- and lineage-specific genes were identified, and ICM/TE cells were sorted according to the patterns of the marker gene expression [ 20 ]. Cells were categorized into lineage groups based on the single cell RNA-seq, and it has been demonstrated that certain conventional lineage markers (e.g., CDX2 and TEAD4 ) do not correspond to markers detected in porcine embryos [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recent studies in cloned embryos showed the dependence of pluripotency‐related and apoptosis gene expression on epigenetic transformations (Samiec, Romanek, Lipiński, & Opiela, ). The single‐cell expression analysis technique pluripotency‐related genes in pig embryos, such as paired box 6 ( PAX6 ) and aquaporin 3 ( AQP3 ), and, in late blastocysts, clathrin adaptor protein ( DAB2 ), platelet‐derived growth factor receptor alpha ( PDGFRA ), fibronectin 1 ( FN1 ), hepatocyte nuclear factor 4 alpha ( HNF4A ), goosecoid homeobox ( GSC ), nuclear receptor subfamily 5 group A member 2 ( NR5A2 ) and lysine acetyltransferase 6A ( KAT6A ) (Wei et al, ). However, the underlying factors involved in pluripotency and its regulation require further study.…”
Section: Pluripotency Transcription Factorsmentioning
confidence: 99%
“…The relative levels of SOX2 and CDX2 mRNA were detected by single-cell qPCR. Then, data were further analyzed by principal component analysis (PCA) using SIMCA14.1 software [29]. Blastomeres from TE and ICM were identi ed according to the clustering analyses.…”
Section: Identi Cation Of Te and Icm Blastomeres Of Blastocystsmentioning
confidence: 99%